The Linkage of Historical and Theological Approaches in the Historiography of the Islamic Revolution; The case of academic writings - Hassan Hazrati; Mina Avanj (تاریخ نگری و تاریخ نگاری, 2023)
In the field of  Islamic Revolution studies, there are many examples where researchers have used a theological approach in analyzing human events and phenomena. They have tried to make the Islamic Revolution appear sacred. The question of the importance of historiography without theological foundations among historians and academic researchers and whether history has been able to achieve a position independent of theological propositions among them is the subject of the present article. This article examines examples of academic works in the field of historiography of the Islamic Revolution in Iran, each of which has in some way used theological ideas in analyzing the events related to the Islamic Revolution. Although the theological approach has been of primary interest to many seminary scholars in their consideration of the Islamic Revolution, a critical examination of these works reveals that the adoption of this approach is not limited to seminary scholars. For many researchers who studied the Islamic Revolution in the academic and university environment, the historical approach is not the mainstay and there is little adherence to the principles and criteria of historical methodology. Therefore, it can be said that there is still no scientific approach to the knowledge of history among many academics and experts.